CYCLOOXYGENASE-2 CATALYSIS AND INHIBITION IN LIPID BILAYER NANODISCS - Orlando, Benjamin J. (2014)
Cyclooxygenases (COX-1 and COX-2) oxygenate arachidonic acid (AA) to generate prostaglandins. The enzymes associate with one leaflet of the membrane bilayer. We utilized nanodisc technology to investigate the function of human (hu) COX-2 and murine (mu) COX-2 in a lipid bilayer environment. huCOX-2 and muCOX-2 were incorporated into nanodiscs composed of POPC, POPS, DOPC, or DOPS phospholipids. Size-exclusion chromatography and negative stain electron microscopy confirm that a single COX-2 homodimer is incorporated into the nanodisc scaffold. Nanodisc-reconstituted COX-2 exhibited similar kinetic profiles for the oxygenation of AA, eicosapentaenoic acid, and 1-arachidonoyl glycerol compared to those derived using detergent solubilized enzyme. Moreover, changing the phospholipid composition of the nanodisc did not alter the ability of COX-2 to oxygenate AA or to be inhibited by various nonselective NSAIDs or celecoxib. The cyclooxygenase activity of nanodisc-reconstituted COX-2 was reduced by aspirin acetylation and potentiated by the nonsubstrate fatty acid palmitic acid to the same extent as detergent solubilized enzyme, independent of phospholipid composition. The stabilization and maintenance of activity afforded by the incorporation of the enzyme into nanodiscs generates a native-like lipid bilayer environment to pursue studies of COX utilizing solution-based techniques that are otherwise not tractable in the presence of detergents.